British soft power: comparative analysis of instruments, mechanisms and practices - Elena M. Kharitonova (Сравнительная политика, 2016)
Abstract: The article examines today’s British soft power goals and objectives, analyses infl uencing factors, political and institutional aspects. The author focuses on the developing perspectives on the roles and participation of non-state actors soft power policies, the ways of measuring effectiveness of such policies. The author compares the approaches of British executive and legislative bodies towards the concept, brings examples of soft power initiatives in the United Kingdom foreign policy and determines specifi c features of the British initiatives in comparison with other countries.